Assessing National Competitive Superiority : An Importance-Performance Matrix Approach - Leong, Siew Meng (Institutional Knowledge at Singapore Management University, 1991)
It is well-accepted that effective strategy is founded on continuous and diagnostic monitoring of one's competitive position. Evidence revealing the skills and resources affording the greatest leverage on future cost and differentiation advantages is particularly critical. Businesses that succeed are those which develop distinctive competences and manage for lowest delivered cost or differentiation through superior customer value.